LEXICAL AND MORPHOLOGICAL MEANS OF EXPRESSING PLACE RELATION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
In this article, we deeply analyze lexical and morphological means of expressing place relation.